A Fast Computational Framework for Seismic Random Response of Multi-support Structures. (2017) - Du, Xianting; Xia, He; Qiao, Hong
Abstract: This paper presents a fast computational framework for seismic random response of multi-support structures, of which computational efficiency handers its application to practical engineering. First of all, after structural modelling based on the finite element method, the large mass method is used to exert the load on the supports in the form of seismic acceleration history, which ensures that the equations of motion of the system are solved directly. Secondly, the impulsive load is exerted on the supports and corresponding dynamic analysis is carried out. On the basis of the impulsive response, a generalized frequency response function (FRF) can be obtained via the Fourier transform. Thirdly, according to classic formulation, auto power spectrum density (PSD) functions of structural response may be calculated, which involves the generalized FRFs and the PSD function matrix of the seismic accelerations at the supports. The proposed framework is verified by comparing its computational results with the analytical solution of a single DOF system. A 5-span bridge during earthquakes is taken as a case study. The results show that three factors influencing spatial variation of seismic ground motion should be taken into consideration to get safer random response of a multi-support structure.